A comprehensive stability indicator for banks - Robert Powell; Duc Hong Vo (Risks, 2020)
Stability indicators are essential to banks in order to identify instability caused by adverse economic circumstances or increasing risks such as customer defaults. This paper develops a novel comprehensive stability indicator (CSI) that can readily be used by individual banks, or by regulators to benchmark financial health across banks. The CSI incorporates the three key risk factors of Creditworthiness, Conditions and Capital (3Cs), using a traffic light system (green, orange and red) to classify bank risk. The CSI achieves similar outcomes in ranking the risk of 20 US banks to the much more complex US Federal Reserve Dodd–Frank stress tests.
Keywords: 330; credit risk; banks; capital; financial stability